2015
DOI: 10.1111/apa.13086
|View full text |Cite
|
Sign up to set email alerts
|

Patients with lymphatic malformations who receive the immunostimulant OK‐432 experience excellent long‐term outcomes

Abstract: OK-432 treatment resulted in a successful outcome in 70% of patients with lymphatic malformations. The long-term outcome was comparable to the short-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…One of the most safe and effective ways of cystic LMs treatment in children is the OK-432 sclerotherapy [5,16]. The OK-432 (Chugai Pharmaceuticals, Tokyo, Japan) is a lyophilized powder of Streptococcus pyogenes (group A, type 3, Su strain) incubated with benzylpenicillin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most safe and effective ways of cystic LMs treatment in children is the OK-432 sclerotherapy [5,16]. The OK-432 (Chugai Pharmaceuticals, Tokyo, Japan) is a lyophilized powder of Streptococcus pyogenes (group A, type 3, Su strain) incubated with benzylpenicillin.…”
Section: Discussionmentioning
confidence: 99%
“…The OK-432 is not exactly a sclerosing agent, because it doesn't destroy vascular endothelium. The OK 432 induces apoptosis of lymphatic endothelium and local cellular inflammatory reaction [7,16]. Recent studies have proved that the pathway of the OK-432 action within lymphangiomas is probably cellular and cytokine-mediated [7,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Three in 4 patients with diffuse lesions involving nearly the entire face had fair or poor therapeutic effects. They were given sirolimus at a dose of 0.8 mg/m 2 , taken twice daily at the internal of 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…[18] One major complication of OK-432 use is delayed swelling and higher fever. Ghaffarpour et al [11] reported 5 patients with readmisson to the hospital as a result of major swelling after injection. In addition, the use of OK-432 is forbidden in patients who are allergic to penicillin.…”
Section: Introductionmentioning
confidence: 99%